2016
DOI: 10.1007/s40825-015-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contributions of Mobile Sources to Air Pollutant Emissions in Tehran, Iran: an Emission Inventory Approach

Abstract: Tehran, a city with 8.5 million inhabitants, has suffered from rapid and unplanned urbanization in recent years resulting in substantial environmental impacts perhaps foremost of which is poor air quality. A major source of air pollution is emissions from mobile vehicles; therefore, having an accurate and comprehensive mobile source emission inventory is essential for decision-makers to develop mitigating strategies. The aim of this study is to determine the relative contributions of specific mobile sources to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 38 publications
(50 reference statements)
2
50
0
Order By: Relevance
“…Tehran as the capital and most populous city of Iran has faced intense ambient air pollution, particularly criteria air pollutants (PM 10 , PM 2.5 , O 3 , NO 2 , SO 2 and CO), in the last two decades due to unsustainable development of industrialization and urbanization, the ever-growing automotive fleet and their emissions alongside ineffective national ambient air quality standards and Middle Eastern dust storm [3][4][5][6] . In fact, ambient air pollution in Tehran has become one of the most challenging environmental issues for Iranian central government, authorities, policy-makers, Tehran citizens, national and international researchers 3,[7][8][9] . It is estimated that approximately 98% of CO, 75% of PM 2.5 and 46% of NO X are emitted from mobile sources in Tehran 4,10 , confirming the need for appropriate sustainable control policies and regulations against vehicular traffic, such as mandatory applying state-of-the-art technologies to reduce road traffic-related emissions, and more effective and serious implementation of transportation policies 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tehran as the capital and most populous city of Iran has faced intense ambient air pollution, particularly criteria air pollutants (PM 10 , PM 2.5 , O 3 , NO 2 , SO 2 and CO), in the last two decades due to unsustainable development of industrialization and urbanization, the ever-growing automotive fleet and their emissions alongside ineffective national ambient air quality standards and Middle Eastern dust storm [3][4][5][6] . In fact, ambient air pollution in Tehran has become one of the most challenging environmental issues for Iranian central government, authorities, policy-makers, Tehran citizens, national and international researchers 3,[7][8][9] . It is estimated that approximately 98% of CO, 75% of PM 2.5 and 46% of NO X are emitted from mobile sources in Tehran 4,10 , confirming the need for appropriate sustainable control policies and regulations against vehicular traffic, such as mandatory applying state-of-the-art technologies to reduce road traffic-related emissions, and more effective and serious implementation of transportation policies 4 .…”
mentioning
confidence: 99%
“…Similar to other O 3 -precursors (NO X and CO) in Tehran, VOCs are mainly emitted from mobile sources (approximately 86%) 4,13 . To date, numerous investigations have been conducted in Tehran that have focused on various issues of ambient air pollution, including investigation of chemical characterization of ambient particulate matter 14,15 and their toxicological effects 16 , ambient particulate matter source apportionment 10 , health effects of ambient air pollutants 3,17 and emission inventory of ambient air pollutants 7 . Although remarkable investigations have been conducted, a comprehensive and in-depth understanding temporal variability of all criteria air pollutants as well as the meteorological influences on their concentrations using a robust method remains unclear in Tehran to date.…”
mentioning
confidence: 99%
“…Ambient PM sampling was performed at two residential sampling locations in central Tehran. [39,41,45]. Therefore, both of the sampling sites of this study are exposed to all of the abovementioned sources, as identified by our previous PM 2.5 source apportionment study [46,50] at the same sampling sites.…”
Section: Sampling Sites Descriptionmentioning
confidence: 84%
“…Therefore, both of the sampling sites of this study are exposed to all of the abovementioned sources, as identified by our previous PM 2.5 source apportionment study [46,50] at the same sampling sites. In addition, considering that the vast majority of the Tehran population lives in/near the city center [39], it can be argued that our sampling sites properly represent the population exposure to major sources of air pollution in the metropolitan area of Tehran. Figure 1 illustrates the map of the study area with the locations of our sampling sites.…”
Section: Sampling Sites Descriptionmentioning
confidence: 99%
See 1 more Smart Citation